¡Solidaridad con el Uruguay! Libertad para Liber Seregni, presidente del Frente Amplio Patriota y líder popular (Consejo Mundial de la Paz)
Black and white poster; portrait of Liber Seregni Poster advertising solidarity with Uruguay and campaigning for the release of Liber Seregni from prison PO-0223